2015
DOI: 10.1080/15389588.2015.1040877
|View full text |Cite
|
Sign up to set email alerts
|

Predicting vehicle belt fit for children ages 6–12

Abstract: Based on this geometric analysis, the rear seats of most vehicles are unlikely to provide good lap belt fit for up to 75% of children ages 6-12. Shoulder belt fit is outside the target range for 40% of children. Consequently, children under 12 years of age are likely to experience markedly poorer belt fit when transitioning out of a booster seat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Both lap belt and shoulder belt fit varied across the boosters, with no observable effect of seat cushion length. Differences in lap belt measures between no-booster and booster conditions were smaller in the current study compared to those measured in past studies [10,14,15]. Since these test conditions encompassed a wider range of seat cushion lengths than in previous studies, this smaller measure may be the result of differences in parameterization of the mockup test conditions.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Both lap belt and shoulder belt fit varied across the boosters, with no observable effect of seat cushion length. Differences in lap belt measures between no-booster and booster conditions were smaller in the current study compared to those measured in past studies [10,14,15]. Since these test conditions encompassed a wider range of seat cushion lengths than in previous studies, this smaller measure may be the result of differences in parameterization of the mockup test conditions.…”
Section: Discussioncontrasting
confidence: 77%
“…Table 1 summarizes the belt anchorage locations and angles selected for use with the reconfigurable mockup relative to the fleet measurements reported by Reed and Ebert [22]. Upper anchorage (shoulder belt D-ring) location was quantified using side-view (XZ) and front-view (YZ) angles of the vector from the seat H-point on the centerline to the D-ring bolt [15]. Mockup Condition C had a belt geometry that matched the geometry of a modified FMVSS No.…”
Section: Mockup Test Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After children grow out of harness systems, booster seats help to adequately restrain children in the years they are not yet ready for the seat belts outfitted in vehicles. For example, without a booster seat, the rear seats of most vehicles are unlikely to provide good lap belt fit for up to 75% of children ages 6–12, and the shoulder belt fit is outside the target range for 40% of children [6]. …”
Section: Introductionmentioning
confidence: 99%
“…The need for a booster seat is largely dependent on the seat structure within vehicles. Geometrical analysis has suggested that most vehicles are unlikely to produce a good lap belt fit for 75% of children aged six to 12, and that children under the age of 12 are very likely to experience poor seatbelt fit after transitioning out of a booster seat [ 8 ]. Nevertheless, most existing legislation does not mandate booster seat use beyond eight years of age (for examples, see [ 9 , 10 , 11 ]).…”
Section: The Importance Of Booster Seats and Bicycle Helmetsmentioning
confidence: 99%